2011
DOI: 10.1016/j.jvs.2011.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Technical and clinical success after endovascular therapy for chronic type B aortic dissections

Abstract: Endovascular treatment (EVT) in chronic type B dissections has a high technical success rate and low mortality/morbidity. However reintervention rates are not negligible which might reduce the clinical success of EVT. Future investigations should aim at identifying patients who benefit from EVT at better defining the timing of EVT and at determining if entry sealing alone is sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…Our serological study probably covered an appropriate time course and indicated no significant change of parameters with no complications, which supports the notion that endovascular repair is rather less aggressive with insignificant inflammatory modulation and may complementary to some promising early results of recent clinical studies [5], [6], [18][21]. Until now, there were only two published studies concerning the inflammatory response in the thoracic aortic pathology after endoluminal stenting but without data on the exact changes of the most important pro-inflammatory mediators at the peri-operative stage [22], [23].…”
Section: Discussionsupporting
confidence: 84%
“…Our serological study probably covered an appropriate time course and indicated no significant change of parameters with no complications, which supports the notion that endovascular repair is rather less aggressive with insignificant inflammatory modulation and may complementary to some promising early results of recent clinical studies [5], [6], [18][21]. Until now, there were only two published studies concerning the inflammatory response in the thoracic aortic pathology after endoluminal stenting but without data on the exact changes of the most important pro-inflammatory mediators at the peri-operative stage [22], [23].…”
Section: Discussionsupporting
confidence: 84%
“…Currently, there is no published or ongoing randomized controlled trial that investigates the biomechanical impact of different thoracic stent-grafts, and only a few studies have compared their clinical performance. [171][172][173] This lack of knowledge calls for a deeper investigation of the performance and behavior of different types of thoracic stent-grafts.…”
Section: Discussionmentioning
confidence: 99%
“…6,22 In our experimental model, we observed five animals with chronic dissections. Of these, three (60%) survived for more than 14 days without any symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Despite the progress in surgical techniques, perioperative complications and operative mortality remain high in patients with type B aortic dissection. 5 Recently, stent graft placement has become a popular minimally invasive therapy for the treatment of type B aortic dissection [4][5][6][7][8] ; however, this therapeutic method has certain limitations and is not yet established as a standard therapy. There have been several attempts to create aortic dissection models in animals with surgical procedures; these have certainly contributed to the development of advanced therapies.…”
mentioning
confidence: 99%